Steve Jobs - Isaacson, Walter (New York : Simon & Schuster, 2011)
Based on more than forty interviews with Jobs conducted over two years, as well as interviews with more than a hundred family members, friends, adversaries, competitors, and colleagues, the author has written a riveting story of the roller-coaster life and searingly intense personality of a creative entrepreneur whose passion for perfection and ferocious drive revolutionized six industries: personal computers, animated movies, music, phones, tablet computing, and digital publishing. Although Jobs cooperated with this book, he asked for no control over what was written nor even the right to read it before it was published. He put nothing off-limits. He encouraged the people he knew to speak honestly. And Jobs speaks candidly, sometimes brutally so, about the people he worked with and competed against. His tale is instructive and cautionary, filled with lessons about innovation, character, leadership, and values. -- From publisher.
Includes bibliographical references and index.
Keywords: Jobs, Steve, -- 1955-2011.; Apple Computer, Inc. -- History; Computer engineers -- United States -- Biography; Chief executive officers -- United States -- Biography